2020
DOI: 10.1113/jp280031
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in fatigability following exercise normalised to the power–duration relationship

Abstract: Key points Knee‐extensors demonstrate greater fatigue resistance in females compared to males during single‐limb and whole‐body exercise. For single‐limb exercise, the intensity–duration relationship is different between sexes, with females sustaining a greater relative intensity of exercise. This study established the power–duration relationship during cycling, then assessed fatigability during critical power‐matched exercise within the heavy and severe intensity domains. When critical power and the curvatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
5
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 112 publications
7
69
5
3
Order By: Relevance
“…Consistently in the studies by Ansdell et al. (2019a, 2020), it was demonstrated that for an equivalent duration of high‐intensity exercise, females experienced less contractile dysfunction than males, potentially indicative of less disruption to the muscle metabolic environment and, perhaps, less of an adaptive stimulus for an equivalent amount of work. Evidence from proton magnetic resonance spectroscopic techniques during isometric exercise modalities would support this notion, indicating greater acidosis (Russ et al., 2005); however, equivalent data during locomotor exercise are difficult to obtain and, as yet, it is unknown whether the same phenomenon occurs.…”
Section: The Acute and Chronic Implications Of Sex Differencessupporting
confidence: 79%
See 2 more Smart Citations
“…Consistently in the studies by Ansdell et al. (2019a, 2020), it was demonstrated that for an equivalent duration of high‐intensity exercise, females experienced less contractile dysfunction than males, potentially indicative of less disruption to the muscle metabolic environment and, perhaps, less of an adaptive stimulus for an equivalent amount of work. Evidence from proton magnetic resonance spectroscopic techniques during isometric exercise modalities would support this notion, indicating greater acidosis (Russ et al., 2005); however, equivalent data during locomotor exercise are difficult to obtain and, as yet, it is unknown whether the same phenomenon occurs.…”
Section: The Acute and Chronic Implications Of Sex Differencessupporting
confidence: 79%
“…In two recent experiments that took the threshold normalization approach, one single‐limb (Ansdell et al., 2019a) and one cycling exercise (Ansdell et al., 2020), a consistent finding was that for the same duration and intensity of exercise, females experienced approximately half the reduction in contractile function of males in the knee extensors at the end of the fatiguing exercise (e.g. Figure 3b).…”
Section: Sex Differences In the Integration Of Physiological Systems mentioning
confidence: 78%
See 1 more Smart Citation
“…As a result, males and females could experience substantial differences in time to task failure, which would be a serious limitation as the intensity and duration of the exercise task are known to influence the magnitude and aetiology of neuromuscular fatigue (Ducrocq et al 2021). In order to circumvent this limitation, Ansdell et al (2020a) normalized exercise intensity to critical power, a metabolic threshold derived from the power-time relationship, with the intention to match the metabolic rate between males and females.…”
Section: How To Normalize Exercise Intensity In Order To Compare Male and Female Physiology?mentioning
confidence: 99%
“…However, similarly to other research areas, sex differences in neuromuscular fatigue are still under-investigated (Hunter, 2016). In a recent article published in The Journal of Physiology, Ansdell and colleagues aimed to clarify the sex differences in fatigue during whole-body exercise (Ansdell et al 2020a).…”
mentioning
confidence: 99%